Atherogenic Dyslipidemia and Cardiovascular Risk Factors in Obese Children - Ebe D’Adamo; Ornella Guardamagna; Francesco Chiarelli; Andrea Bartuli; Daniela Liccardo; Federica Ferrari; Valerio Nobili (International Journal of Endocrinology)
Childhood obesity when associated with serum lipoprotein changes triggers atherosclerosis. Evidences suggest that the atherosclerotic process begins in childhood and that the extent of early atherosclerosis of the aorta and coronary arteries can be associated with lipoprotein levels and obesity. Furthermore, many studies in childhood demonstrate an important relationship between parameters of insulin sensitivity, body fat distribution, and the development of lipid abnormalities. This review focuses on the most recent findings on the relationship between obesity, dyslipidemia, and cardiovascular risk in children.